Effect of Glide Path Preparation on Centering Ability and Canal Transportation of Blue-Treated Flat-Designed Single File Systems - Hadrian, Gary; Suwartini, Tien; Ratnasari, Dina; Budiman, Johan Arief (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2026)
Maintaining the original root canal anatomy during shaping is crucial to prevent procedural errors, such as canal transportation and ledge formation. The development of heat-treated blue NiTi instruments can improve flexibility, resistance to cyclic fatigue, and the ability to maintain root canal curvature. This study aimed to evaluate the effect of glide path (GP) on canal centering and canal transportation using a single-file system of blue NiTi with a conventional S-shaped cross-section design (AF S) and a flat design (AF F). Forty J-shaped canal simulation resin blocks were randomly divided into four groups: AF F+GP, AF F, AF S+GP, and AF S (n = 10 each group). In the group using the glide path (AF F+GP and AF S+GP), ProGlider #16.02 was used before instrumentation. Pre- and post-instrumentation images were analyzed using Adobe Photoshop CS6 software to measure canal centering and transportation at the apical, middle, and coronal thirds. Data were analyzed using one-way ANOVA and Tukey’s post hoc test (p<0.05). Significant differences were found in canal centering and canal transportation in the apical and middle thirds (p<0.05), while no significant differences were found in the coronal third (p>0.05). The use of a glide path significantly improved centering ability and reduced transportation. Furthermore, the flat design of the Blue NiTi single-file system demonstrated better centering ability and reduced canal transportation than conventional S-shaped systems. All systems could shape curved simulated root canals without iatrogenic error.